Plasma homocysteine in Alzheimer's disease with or without co-morbid depressive symptoms - Kitzlerová, Eva; Fisar, Zdenĕk; Jirák, Roman; Zvĕrová, Martina; Hroudová, Jana; Benaková, Hana; Raboch, Jirí (Neuro endocrinology letters, 2014)
OBJECTIVE: Elevated homocysteine is associated with a variety of diseases, including Alzheimer's disease (AD) and depressive disorder. This study was designed to detect an association between plasma homocysteine and AD with or without co-morbid depressive symptoms. METHODS: Plasma homocysteine concentrations were measured in 85 AD patients (36 of them with depressive symptoms), 33 non-AD patients with a depression diagnosis and 44 healthy controls, all aged above 50 years. RESULTS: Positive correlation between age and homocysteine was confirmed. Significantly higher mean plasma homocysteine was found in AD patients, but not in depressive patients, when compared with controls. We confirmed significant correlation between homocysteine concentration and the degree of cognitive impairment in AD patients. There was no incremental effect of concurrent depressive symptoms on homocysteine concentration in AD patients. CONCLUSION: The association of high homocysteine with degree of cognitive impairment or stage of dementia in AD indicate potential role of high plasma homocysteine as a biomarker of the disease and/or indicator of brain damage during the progression of AD dementia.
Keywords: senioři; stupeň závažnosti nemoci; senioři nad 80 let; komorbidita; homocystein; Middle Aged; mužské pohlaví; Alzheimer Disease; depresivní poruchy; Homocysteine; věkové faktory; Aged, 80 and over; ženské pohlaví; Humans; biologické markery; Comorbidity; lidé středního věku; Age Factors; Alzheimerova nemoc; Biomarkers; Female; Aged; Severity of Illness Index; Depressive Disorder; lidé; Male